Bayan Tafsir - Muhammad Zaini (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Many verses of the Qur’an having general meanings indicate that it is a global holy book which covers all aspects of life. It is a God’s mercy to all mankind in the universe. In fact, the verses of the Qur’an having generl meanings have been explained by the Qur’an itself because one verse explains another verse, yufassiru ba`dhuhu ba’dhan. This means the general meaning verses are not contradictory one to each other that during the Prophet time, Rasulullah peace be upon him explained the meanings of the Qur’an and applied it in his daily life together with his companions. In this context, the Prophet functions as the mubayyin (explainer) of the Qur’an either in his sayings, actions or permissions.